Design and Analysis of Under Ground Water Tank Considering Different Fill Conditions Using STAAD.PRO - Gadekar, Deepshikha; Patel, Rakesh (International Journal of Scientific Research in Civil Engineering, 2022)
Water tanks and reservoirs are used to store liquids like water, petroleum or chemicals. For any domestic and commercial purposes, water tanks are very basic need to meet their day to day use. In this project an attempt is made to design the rectangular underground tank, the tank is to maintain atmospheric temperature and provided optimum height for easy pumping of water to overhead tank. Since it is underground water tank the lateral earth pressure and water pressure also considered for the design calculations, so the design is to be carried out as per IS code norms. This project deals with analysis and design of under ground water tank of 2lakh liter capacity. The design in this project comprises of side walls, base slab and roof slab. The analysis and design of underground water tank is done using staad.pro. For this design project limit state method is used.
Keywords: Analysis; Water Tank; Structure; Forces; Moment; Deflection